Penerapan Teknologi Berbasis Sistem Informasi Terhadap Penggunaan Transaksi Pembayaran QRIS Dalam Meningkatkan Efisiensi Operasional - Shella Shella; Elisa Elisa; Epehulisa Br Ginting; Everlin Everlin; Nosperiani Halawa; Shelia Shelia; Zona Kharisma Sinta (Politeknik Raflesia Press, 2025)
This study aims to analyze the opportunities and challenges in implementing QRIS as a digital payment method for MSMEs in Tepi Laut Tanjungpinang. With the increasing trend of cashless transactions, this research explores the benefits, obstacles, and optimization strategies for QRIS adoption among small and medium enterprises. The research method used is a qualitative approach through direct observation and interviews with several MSMEs that have adopted QRIS, such as Pisang Kembung Viral, Es Jeruk Kiamboy, MK Dimsum, Teh Tarik Malaysia Brother, and Corndog Tarik Lumer. The phenomenon underlying this research is the rising adoption of digital payments among MSMEs, which still faces various challenges, such as customer preference for cash and technical transaction issues. The findings indicate that QRIS offers multiple benefits for MSMEs, particularly in enhancing operational efficiency, speeding up transactions, and facilitating financial record-keeping. However, challenges persist, including technical constraints and administrative fees that may reduce business profits. The conclusion of this study highlights the importance of customer education, selecting QRIS service providers with lower administrative costs, and improving infrastructure to ensure smooth digital transactions. As recommendations, MSMEs are encouraged to actively promote QRIS usage among customers, collaborate with digital financial service providers, and leverage social media to expand cashless transactions.